The impact of screen access associated with hospital admissions for migraine in children and adolescents - Bezerra, Isabella Campos; Parente, Enzo Lima Alcântara; Araújo, Marisa Bezerra de; Pinheiro, Marcelo de Almeida (Headache Medicine, 2023)
Full abstract in PDF.